A case of methotrexate‐associated Epstein‐Barr virus‐positive mucocutaneous ulcer - Sakamoto, Keiko; Baba, Takeshi; Takatori, Hiroaki; Nagao, Keisuke; Misawa, Junko; Honda, Tetsuya (Skin Health and Disease, 2022)
Epstein‐Barr virus‐positive mucocutaneous ulcer (EBVMCU) is a B‐cell proliferative disorder that has been designated as a provisional entity in the 2017 World Health Organization classification for lymphoid neoplasms. While EBVMCU may contain varying numbers of cells with Hodgkin and Reed‐Sternberg cells‐like morphology, the clinical course is benign and must be distinguished from lymphomas. Patients who develop EBVMCU are commonly immunocompromised, with methotrexate (MTX) as the leading cause. Most previously reported cases of EBVMCU describe mucosal ulcers with very little documentation on skin lesions and its course. Here, we report a case of MTX‐associated EBVMCU of the lower leg that underwent spontaneous regression after MTX withdrawal, during which negative conversion of local Epstein‐Barr virus activation was confirmed.